Antibacterial textile coatings with strategies for long-term performance and environmental safety - Nurul Hidayah, Abu Bakar; Wan Norfazilah, Wan Ismail; Umair, Muhammad (Elsevier B.V., 2025)
Antibacterial coatings are transforming the textile industry by meeting the rising demand for hygienic and multifunctional fabrics in healthcare, sportswear and home textiles. These coatings inhibit microbial growth, control odor and enhance fabric durability. Among various strategies, nanocomposite-based coatings, particularly those incorporating metal nanoparticles such as silver and copper, exhibit strong antibacterial properties but face challenges related to environmental toxicity and diminished efficacy after repeated laundering. In contrast, biopolymer-based coatings that utilize materials like chitosan and alginate offer eco-friendly alternatives but struggle with long-term performance. Recent advances in hybrid organic/inorganic systems, nanocomposite coatings and superhydrophobic surfaces offer promising ways to overcome these challenges and deliver durable, sustainable antibacterial solutions. This review examines the mechanisms, materials and realworld performance of antibacterial fabric coatings, with a focus on innovations such as plasma pretreatment, crosslinking agents and multifunctional designs. Emphasis is placed on the need for environmentally safe, scalable and cost-effective technologies to meet the growing global demand for durable antibacterial textiles. The review highlights the need to develop coatings that maintain antibacterial effectiveness after repeated washing and environmental exposure to ensure long-term performance and sustainability.